Optimal double acceptance sampling inspection plans based on inverted Nadarajah-Haghighi distribution - Mehran Naghizadeh Qomi; Zohre Mahdizadeh (تصمیم گیری و تحقیق در عملیات)
Purpose: In this paper, we present optimal single acceptance sampling inspection plans for Inverted Nadarajah-Haghighi distribution so that the consumer’s and producer’s risks are controlled simultaneously.Methodology: Nonlinear optimization program is used to obtain the optimal sample size and acceptance number as well as the associated consumer’s and producer’s risks.Findings: Optimal sample size and acceptance number are obtained in generalized half-normal distribution. Two real data sets are given for illustrating the results.Originality/Value: Two-point method is used to find the best plan by using nonlinear programing optimization problem. All computations are performed by the R software.